2007
DOI: 10.1159/000108103
|View full text |Cite
|
Sign up to set email alerts
|

Nectin and Nectin-Like Molecules: Biology and Pathology

Abstract: Nectins and nectin-like molecules (Necls) are structurally related transmembrane proteins primarily involved in cell adhesion. Nectins and afadin, the adaptor or anchoring protein, stabilize the epithelium and endothelium and establish apical-basal polarity of epithelial cells, independently or in cooperation with other cell adhesion molecules. Necls facilitate cell–cell communication implicated in cell movement and proliferation, immune responses, and cancer cell phenotypes. Necls interact with nectins and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 227 publications
(156 reference statements)
1
45
0
Order By: Relevance
“…After sequestration of cadherins at the adherens junction, nectins continue to regulate cadherin function by (i) inhibiting the endocytosis of cadherin and (ii) affecting the conformation of cadherin extracellular domains to facilitate trans-interactions (Hoshino et al, 2005;Sato et al, 2006). Nectins also regulate cytoskeletal dynamics via F-actin binding proteins that interact directly with nectin [e.g., afadin, ␣-catenin, ␣-actinin, vinculin, annexin II and IQGAP Miyoshi and Takai, 2007)] (Fig. 1), and establishment of nectin-based adherens junctions required annexin II and IQGAP in MDCK cells (Katata et al, 2003;Yamada et al, 2005aYamada et al, , 2006a.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
“…After sequestration of cadherins at the adherens junction, nectins continue to regulate cadherin function by (i) inhibiting the endocytosis of cadherin and (ii) affecting the conformation of cadherin extracellular domains to facilitate trans-interactions (Hoshino et al, 2005;Sato et al, 2006). Nectins also regulate cytoskeletal dynamics via F-actin binding proteins that interact directly with nectin [e.g., afadin, ␣-catenin, ␣-actinin, vinculin, annexin II and IQGAP Miyoshi and Takai, 2007)] (Fig. 1), and establishment of nectin-based adherens junctions required annexin II and IQGAP in MDCK cells (Katata et al, 2003;Yamada et al, 2005aYamada et al, , 2006a.…”
Section: A Cell-cell Actin-based Adherens Junctionsmentioning
confidence: 99%
“…Homotypic trans-dimerization of E-cadherin is crucial for initiation of cellcell contact, whereas homotypic cis-dimerization is required for stabilization of adherens junctions (Wu et al, 2010). In addition to E-cadherin, another class of transmembrane proteins, nectins, have been recently identified as cell adhesion molecules in adherens junctions (Miyoshi and Takai, 2007;Takai et al, 2003). Nectins are thought to initiate cell-cell contact by forming hetero-trans dimers even before E-cadherin dimerization, which is then elaborated by nectin-facilitated cadherin recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in previous studies, it has been demonstrated that alterations of E-cadherin or integrins are frequently observed in RCCC. 5,6 We previously identified a tumor suppressor gene, CADM1/ TSLC1, in human nonsmall cell lung cancer (NSCLC). 7 The CADM1 is expressed in most epithelial tissues, while its expression is frequently lost in many tumors, including NSCLC or prostate cancer.…”
mentioning
confidence: 99%